Characterization of the guinea pig (Cavia porcellus) meat for fermented sausage preparation (2017)
Guinea pig meat, due to its high nutritional value, is important in the human diet, and is a key product for food safety; additionally, this meat is used in the agroindustry production, and people who consume it are less prone to diseases. The objective of the investigation was to characterize the guinea pig meat, for its possible use in the elaboration of an improved fermented sausage. The lines of guinea pig evaluated were the Creole, Andean and Peruvian.Meat was characterized using analysis of variance for differences and means comparison, according to Duncan (p<0,05), from a physicochemical, microbiological and sensorial point of view. The moisture content did not show differences between the three evaluated lines, whose values were 75.6 % in the Andean, 73.3 % in the improved Peruvian, and 72.7 % in the Creole. The highest protein content was 19.1 % in the Creole, which also had the lowest fat content (7.6 %). In regard to the meat microbiological and sensorial characteristics, it complied with the quality requirements established by the respective standards. The guinea pig meat quality allows its use in a meat product formulation.